2014
DOI: 10.2298/jas1403227b
|View full text |Cite
|
Sign up to set email alerts
|

Genetic gains in three breeding eras of maize hybrids under low and optimum nitrogen fertilization

Abstract: A comparative study on the response of six maize hybrids: two hybrids each from the 1980s (8321-21 and 8425-8), 1990s (9801-11 and 9803-2) and 2000s (0103-11 and 0103-15) to sub-optimal and optimal nitrogen fertilization was conducted in Oke-Oyi, Nigeria. The trials were set up in a split plot with three nitrogen levels (0, 30 and 90 kg N ha -1 ) as a main plot and six hybrids as sub-plots. Significant interactions were observed between hybrid and N level for all characters, with increasing in variation as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 31 publications
2
11
0
1
Order By: Relevance
“…It was therefore expected that the inbred lines would withstand the drought stress occurring during flowering and grain filling in the savannas of WCA, as had been observed in cultivars of other maturity groups. Results revealed that mean grain yield increased by 48.4 and 62.4%, as N increased from 0 to 30 kg ha −1 and from 30 to 90 kg ha −1 , respectively (Bello et al, 2014). We recognized at the very early stages of the IITA extra-early maize improvement program that several genes governed the expression of drought tolerance in maize.…”
Section: Development Of Extra-early Cultivarsmentioning
confidence: 79%
See 3 more Smart Citations
“…It was therefore expected that the inbred lines would withstand the drought stress occurring during flowering and grain filling in the savannas of WCA, as had been observed in cultivars of other maturity groups. Results revealed that mean grain yield increased by 48.4 and 62.4%, as N increased from 0 to 30 kg ha −1 and from 30 to 90 kg ha −1 , respectively (Bello et al, 2014). We recognized at the very early stages of the IITA extra-early maize improvement program that several genes governed the expression of drought tolerance in maize.…”
Section: Development Of Extra-early Cultivarsmentioning
confidence: 79%
“…Several extra-early inbred lines in the IITA Maize Program possessed drought escape mechanism(s) and drought tolerance genes. Bello et al (2014) conducted a comparative study on the response of six maize hybrids, two each from the 1980, 1990, and 2000 eras under three N levels (0, 30, and 90 kg N ha −1 ); the N levels were used as main plots and the six hybrids as subplots. Thus, a tremendous opportunity existed for improvement of the performance of the cultivars in the program by introgressing genes for improved tolerance to drought and Striga resistance.…”
Section: Development Of Extra-early Cultivarsmentioning
confidence: 99%
See 2 more Smart Citations
“…Salah satu upaya untuk mengatasi ketersediaan N yang rendah di tanah yaitu menggunakan varietas jagung toleran N rendah (Bello et al 2014;Syafruddin et al 2013;Efendi et al 2014). Jagung hibrida yang toleran terhadap N rendah mampu mengurangi risiko kegagalan panen dan dapat meningkatkan efisiensi pemupukan pada lahan suboptimal (Wegary et al 2014).…”
Section: Pendahuluanunclassified